PENGARUH SPIRITUAL LEADERSHIP WORKPLACE SPIRITUALITY TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Media Pratama; Suryosukmono, Gerry (Jurnal Ilmiah Ekonomi Dan Bisnis, 2024)
Abstract: : This research aims to determine the relationship between spiritual leadership, workplace spirituality and employee performance with job satisfaction as a mediating variable. Data was obtained through distributing questionnaires directly to 255 respondents who were employees of the public works and spatial planning (PUPR) department. The analysis method used is SEM-PLS. The research results also found that job satisfaction has a very significant influence on employee performance. However, spiritual leadership was not proven to have a significant influence on performance, either directly or through job satisfaction as a mediating variable. These findings differ from previous research and suggest that other factors may influence employee satisfaction and performance. This shows that good leadership is not always accompanied by increased employee performance, although job satisfaction can increase. On the other hand, workplace spirituality is proven to have a significant influence on job satisfaction and employee performance Keywords: Spiritual Leadership, Workplace Spirituality, Performance, Job satisfaction